ADAPTIVITY OF COMPLEX NETWORK TOPOLOGIES FOR DESIGNING RESILIENT SUPPLY CHAIN NETWORK - Mari, Sonia Irshad; Lee, Young Hae; Memon, Muhammad Saad; Park, Young Soo; Kim, Minsun (International Journal of Industrial Engineering: Theory, Applications and Practice, 2015)
Supply chain systems are becoming more complex and dynamic as a result of globalization and the development of information technology. The overwhelming number of relations and their interdependencies among each other makes supply chain a complex network which shows highly nonlinear and complex dynamical behaviors. Supply chain network grows and self organizes through complex interactions between their structure and function. This absolute complexity of supply-chain networks, with unavoidable lack of prediction, makes it diﬃcult to manage and control them with the assumption of linearized set of models. This paper will focus on the resilience of supply chain from the perspective of complex network topologies. In this paper, various resilience metrics for supply chain are developed and a resilient supply chain growth model is also developed for designing the supply chain network. The Agent-Based simulation analysis is carried out to test the developed model based on resilience metrics. The results of proposed resilient supply chain growth model are compared with major complex network models. Simulation result shows that supply chain network can be designed based on complex network theory especially as a scale free network. It is also concluded that the proposed model can be more suitable than general complex network models for designing the resilient supply chain network.